2016
DOI: 10.12688/f1000research.9971.1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction with different designs of progressive soft contact lenses in myopes

Abstract: Aim: The purpose of this study was to compare the changes in relative peripheral refractive error produced by two different designs of progressive soft contact lenses in myopic schoolchildren. Methods: Twenty-seven myopic schoolchildren age between 13 to 15 years were included in this study. The measurements of central and peripheral refraction were made using a Grand-Seiko WR-5100K open-field autorefractometer without correction (baseline), and two different designs of progressive contact lenses (PCLs) (Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The treatment zone ( 48 , 49 ) and high-order aberrations ( 50 ) also have important roles in slowing axial elongation. In 2016, Allinjawi et al compared the peripheral retinal hyperopic defocus reductions with two different progressive multifocal contact lens designs and reported that lenses with additional power commencing at 3.5 mm diameter induced significant reduction in the peripheral retinal hyperopic defocus compared with lenses with additional power commencing at 5.0 mm diameter ( 51 ). A recent study demonstrated that a smaller back optic zone diameter for the orthokeratology lens generated a smaller plus power ring diameter on the anterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment zone ( 48 , 49 ) and high-order aberrations ( 50 ) also have important roles in slowing axial elongation. In 2016, Allinjawi et al compared the peripheral retinal hyperopic defocus reductions with two different progressive multifocal contact lens designs and reported that lenses with additional power commencing at 3.5 mm diameter induced significant reduction in the peripheral retinal hyperopic defocus compared with lenses with additional power commencing at 5.0 mm diameter ( 51 ). A recent study demonstrated that a smaller back optic zone diameter for the orthokeratology lens generated a smaller plus power ring diameter on the anterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…One study compared the reduction of the peripheral retinal hyperopic defocus in two different designs of progressive MFCLs. Only the lens with the additional power starting at the 3.5-mm diameter caused a significant reduction in the peripheral retinal hyperopic defocus, while the lens with the additional power starting at the 5.0-mm diameter did not ( Allinjawi et al, 2016 ). Li et al also reported that MFCLs with two concentric defocus rings in the periphery had better myopia control than MFCLs with a single peripheral defocus ring ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the day, this altered corneal front surface induces myopic defocus on the peripheral retina ( Charman et al, 2006 ; Queiros et al, 2010 , 2018 ), and this may be a mechanism for myopia retardation ( Smith et al, 2009 ; Benavente-Perez et al, 2014 ). In contrast, daytime MFCL wear directly imposes peripheral retinal myopic defocus when the lenses are worn ( Sankaridurg et al, 2011 ; Allinjawi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several optical means have attempted to reduce the magnitude of hyperopic peripheral defocus or peripherally impose myopic defocus while maintaining good correction of foveal refractive errors. Orthokeratology, multifocal soft contact lenses, custom-designed rigid gas permeable lenses, and some novel contact lens designs can effectively regulate peripheral refraction in myopic eyes [9][10][11]. If the hypothesis is correct, it is important to quantify the effect of these lenses on imposing peripheral myopic defocus.…”
Section: Introductionmentioning
confidence: 99%